O pacto nacional pela alfabetização na idade certa e a formação docente: entre saberes e fazeres - Souza, Abda Alves Vieira de (2018)
The difficulty of school in literacy has been the greatest problem of education in Brazil. Due to the chronic failure of literacy, the federal government since the 2000s has invested in the promotion of public policies for teacher training, particularly in the area of literacy. The children of the Brazilian public school are literate late, so the goal of the Ministry of Education is to literate children up to 8 years of age. To achieve this goal, the National Pact for Literacy in the Right Age (PNAIC) was created, which is a set of public policies formulated to improve the quality of primary education, among them, teacher education. This research investigates the effectiveness of this training, it seeks to know what actually happens in the practice of literacy teachers, when they undergo a systematic training. The aim of this research is to analyze the teaching knowledge necessary for literacy, noting the extent to which the PNAIC training contributed to the appropriation of teaching methodologies of the alphabetical writing system from the perspective of alphabetizing literacy. To achieve this goal, a case study was developed with two teachers who work in the initial years of Elementary School, in the municipal network of Maceió. The methodological procedures used were: observations in classrooms; analysis of the activities proposed by the teachers; and interviews with teachers. In order to understand the origin and how teachers' knowledge is constructed, the concepts defended by Tardif (2002, 2008) and Gauthier et al (2006) were used. As for the specific knowledge of the literacy field, the studies postulated by Soares (2007, 2014, 2016), Ferreiro, Teberosky (1984), Mortatti (2006) and Morais (2004, 2005, 2012) were used. The results of this research indicate that teachers have plural and heterogeneous knowledge, resulting from initial and continuing education; and unique, from their life histories and professional experiences. In relation to the knowledge needed to literacy, the two teachers hierarchized the same knowledge. As for literacy methods, both teachers make use of methodologies of the school tradition allied to innovative theoretical elements, that is, adapt different didactic strategies to be able to adjust them to reality. These data seem to point out that teachers are not only reproducers of theories learned in the academy but are active in their practice as they adapt the theories to meet the everyday challenges of the classroom. As for the teaching knowledges identified as appropriation of the Pnaic training, the teachers specified the same knowledge as the most significant: reading delight and the didactic sequence. In relation to how teachers work the different axes of Portuguese language teaching in their classroom routines, the results show that it was possible to approximate the work developed by the teachers with the knowledge acquired in the formation of the Pnaic. The data also indicate that, in their daily practices, teachers incorporated activities that help both in the perspective of literacy and literacy, which were not routinely carried out on a daily basis or that were made sporadically, and that the formation of PNAIC favored the introduction of these practices, bringing more theoretical and didactic security.